Mazahib Al-Tafsir: An Axiological And Ontological-Epistemological Investigation In The Context Of Qur'anic Interpretation - Mahfud, Ahmad; Kholid, Abd (Jurnal Ushuluddin, 2025)
The diversity of Qur'ānic interpretations often leads to disputes among Muslims. Therefore, critical evaluation and tolerance are essential to avoid exclusive truth claims and subjective biases, as well as to promote a moderate understanding of the Qur'an. The purpose of this study is to examine the ontological, epistemological, and axiological aspects of mazahib al-Tafsir. It is hoped that common ground and consensus can be established in understanding the teachings of the Qur'an, thereby strengthening ukhuwah Islamiyah and preventing divisions among Muslims. This research employs a descriptive-analytical method to explore the development of mazahib al-Tafsir from classical to contemporary times. Data were collected through a literature review of Tafsir texts and related scholarly works. The findings indicate that, ontologically, mazahib al-Tafsir are schools of Qur'anic interpretation that emerge from the differing backgrounds, understandings, and methodologies of mufassirs. Epistemologically, the evolution of mazahib al-Tafsir is influenced by both internal factors (such as language, politics, and theology) and external factors (including other civilizations and scientific advancements). This has led to the emergence of various styles of tafsir (bil Ma'tsur, bir Ra'yi, and scientific) as efforts to understand and apply the Qur'an in a dynamic context. The axiology of mazahib al-Tafsir aims to avoid the sacralization of religious thought, to comprehend the evolution of Qur'anic interpretation, and to appreciate the plurality of interpretations. Reason: Improved clarity, vocabulary, and technical accuracy while maintaining the original meaning